Antimicrobial activity of ZnO-doxycycline hyclate thermosensitive gel - Phaechamud,T. (Science Society of Thailand under Royal Patronage, 2015)
Zinc oxide (ZnO) is a prototype of micro- and nanomaterials widely studied in different fields due to many promising new applications. Various zinc oxides (typical, micronized, powder, tetrapod I, and tetrapod II ZnO) have been characterized using SEM. The particle size of zinc oxides was analysed using laser light diffraction spectroscopy. Effects of types and amounts of ZnO on the antimicrobial activity were evaluated using Staphylococcus aureus, Escherichia coli, and Candida albicans as standard microbes. Lutrol F127 systems comprising ZnO and doxycycline hyclate were developed. Cytotoxicity of test samples and gel was investigated on human gingival fibroblast and macrophage cell line U937. Particle size analysis revealed that micronized ZnO was smaller than ZnO powder, ZnO BP, tetrapod I, or II zinc oxides. The particle size of tetrapod zinc oxides was larger than the others since they exhibited an arm structure configuration. The antibacterial activity depended on the particle size of ZnO, whereas the antifungal activity was less affected by the particle size. Increasing ZnO in the doxycycline hyclate-Lutrol F127 systems decreased the inhibition zone diameters against all test microbes investigated with agar diffusion method because it retarded drug diffusion. This effect could prolong the doxycycline hyclate release. N-methyl-2-pyrrolidone could enhance the antifungal activity of doxycycline hyclate thermosensitive gel. The developed system could inhibit bacteria in the oral cavity. All 10 mg/ml test samples were not toxic to human gingival fibroblast or macrophage cell line, however Lutrol F127 and doxycycline hyclate showed a slight effect but no significant difference from that of the control group. Therefore, ZnO combined with doxycycline hyclate could prolong the inhibition of microbes in the form of thermosensitive gel to use in localized periodontitis therapy.